Implementasi Budaya 3S dalam Pengawasan Sekolah di SMAN 9 Wajo: Studi Kualitatif - Syamsiar, Syamsiar; Nurcaya, Nurcaya (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
This study aims to analyze the implementation of the 3S culture (sipakatau, sipakalebbi, sipakainge) in carrying out the duties of school supervisors at SMAN 9 Wajo. This research employs a qualitative method with a descriptive approach. The informants consist of the principal and two teachers, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data display, and conclusion drawing, with data validity testing using data and method triangulation. The results show that the 3S culture, which includes sipakatau (humanizing each other), sipakalebbi (glorifying each other), and sipakainge (reminding each other), is effectively implemented in managerial supervision by school supervisors. This supervision includes tasks such as inspection, advising, monitoring, coordination, and reporting, playing a significant role in improving school management.